Assessing the clinical relevance of point-of-care ultrasound for hospitalists: Influence on clinical reasoning and decision-making - Maira Dias Souza; Hassan Rahhal; Iolanda F. L. C. Tibério (PLoS ONE, 2025)
Introduction Point-of-care ultrasonography (POCUS) is increasingly recognized in internal medicine, yet its influence on hospitalists’ clinical reasoning remains underexplored. Objectives This study aimed to evaluate the influence of POCUS on diagnostic hypotheses, management strategies, and confidence levels among hospitalists in a transitional care unit with limited access to advanced imaging. Methods Prospective descriptive study in a transitional care unit enrolling 19 hospitalists. During routine care, clinicians used POCUS at their discretion and, immediately afterward, completed a structured form capturing the clinical question, pre- and post-POCUS diagnostic hypotheses, confidence levels, and management decisions. Per-encounter changes in these parameters were summarized descriptively. Results POCUS led to a change in the primary diagnostic hypothesis in 37% (38/104) of clinical encounters and altered management in 39% (41/104) of cases. Diagnostic confidence increased in 46% (48/104) of instances. Even when the primary hypothesis remained unchanged (62% − 66/104), POCUS strengthened diagnostic confidence in 36% (24/66) of these cases and aided in ruling out alternative diagnoses in 62% (41/66). Notably, POCUS had no discernible influence in only 13% (14/104) of cases. Conclusion This study suggests that POCUS may influence clinical reasoning and decision-making among hospitalists in a setting with limited imaging resources. POCUS frequently led to changes in diagnostic hypotheses and management plans, and often increased diagnostic confidence, even when the initial hypothesis was maintained. These findings suggest that POCUS may play a supportive role in bedside assessment and patient management in internal medicine, underscoring the need for further research and structured training before broader integration.